FORM, METHODS AND TOOLS OF DEVELOPING STUDENTS' AXIOLOGICAL ATTITUDE TO HISTORICAL AND SPIRITUAL IDEALS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article presents some opinions on the form, methods and means of developing students' axiological attitude to historical and spiritual ideals. Also, the article presents some views on the concept of axiological attitude to historical and spiritual ideals.